The «Mercurio Peruano» of Víctor Andrés Belaunde, promoter of the ideals of «El Mercurio» of «los amantes del país» - Zeta Pozo, Rosa (Mercurio Peruano, 2018)
In the analysis of the Peruvian illustration that Christian vision is observed, not outlined in a systematic way, but in diverse essays referring to humanity, to science, to nature. The promotion of the conception of a God as the supreme being and creator of all nature was important; man as a creature of God, the purity of faith, based on the primitive church, the instruction and training of priests; the rigorous, not superficial, indoctrination of the faithful; evangelization, united to the civilization and the humanity of the settlers was important as well.El Mercurio of Victor Andrés Belaunde reflects the same vision in Christian humanism that he proclaims. César Pacheco Vélez states that from 1928, the magazine becomes a platform of Catholic thought and the social doctrine of the Church, but open and generously hospitable to the diverse artistic and literary movement, which were very respectful and always in an attitude of dialogue against other trends and doctrines.